Estudo clínico e radiológico de Parkinsonismo vascular e doença de Parkinson - Thiago Cardoso Vale (2013)
Introduction: Vascular Parkinsonism (VP) is a form of secondary Parkinsonism resulting from cerebrovascular disease. There is a shortage of studies on VP, especially comparative studies between VP and Parkinson's disease (PD) or other Parkinsonian syndromes. A systematic review identified only seven clinical studies that addressed the characteristics that helped clinicians to distinguish VP from PD. These studies have shown that VP patients are, on average, 4 to 10 years older than PD patients at symptom onset. VP patients more commonly present with symmetrical gait difficulties, postural instability, falls, dementia, pyramidal signs, pseudobulbar palsy, and urinary incontinence. PD patients are likewise more rigid and tremulous and tend to have more bradykinesia. Vascular risk factors are more common in VP patients than in those with PD. Objective: To compare the clinical and radiological features of VP and PD. Methods: A cross-sectional study, in which 15 VP patients (eight [53.3%] men; aged 75.7 ± 10.4 years) and 30 PD patients (17 [56.7%] men; aged 67.3 ± 7.5 years) underwent motor (UPDRS and Freezing of Gait scales) and cognitive evaluation (Mini-Mental State Examination, Frontal Assessment Battery and Executive Interview 25 scales) and brain magnetic resonance imaging (MRI). Results: All VP patients had arterial hypertension and they were, on average, 8.4 years older (p = 0.004) and presented with a sudden onset of Parkinsonism (80.0%) and a rapidly progressive clinical course (53.3%). VP patients had more lower body Parkinsonism (p < 0.001), postural instability (p = 0.003) with freezing of gait and falls (p < 0.001), urinary incontinence (p < 0.001), and pyramidal signs (p < 0.001). Tremor (p < 0.001) and psychotic symptoms (p < 0.042) were mostly seen in the PD group. VP patients had higher MDSUPDRS scale scores with statistical significance and greater cognitive impairment with 12 (80.0%) fulfilling criteria for probable vascular dementia. Most VP patients had brain MRI changes: multiple lacunar infarcts (66.7%) or extensive white matter disease (26.7%). Conclusions: VP could be distinguished from PD based on a sudden onset of Parkinsonism at an older age, characterized by lower body predominance, urinary incontinence, pyramidal signs, postural instability with freezing of gait and falls, dementia and multilacunar infarcts or extensive white matter disease on brain MRI.